Determinants of multinational banks' subsidiary performance: the host and home country effects - Sufian, Fadzlan (Emerald Group Publishing Limited, 2012)
Purpose – The purpose of this paper is to provide new empirical evidence on the performance of multinational banks as a subset of the eclectic theory. Design/methodology/approach – The paper employs the least square method of random effects model (REM). The opportunity to use a random effects rather than a fixed effects model has been tested with the Hausman test. To control for cross-section heteroscedasticity of the variables, the study employs White’s transformation. Findings – The empirical findings indicate that credit risk, overhead costs, income from nontraditional sources, and loans intensity contribute positively to the profitability of the foreign subsidiaries. The results seem to suggest that the parent bank’s branch networks exert positive influence on their foreign subsidiaries in India, while the size of the parent banks negatively influences their Indian subsidiaries’ performance. Research limitations/implications – Due to its limitations, the present study could be extended in a variety of ways. First, future research could include more variables such as taxation and regulation indicators, and exchange rates as well as indicators of the quality of the offered services. Second, future studies could also examine the differences in the determinants of profitability between small and large or high and low profitability banks. Third, in terms of methodology, frontier optimization techniques such as the data envelopment analysis, the stochastic frontier analysis, and/or the Malmquist productivity index methods are recommended to examine the performance of the foreign subsidiaries of multinational banks operating in the Indian banking sector. Practical implications – Studies on the potential benefit of foreign bank entry have been studied extensively. Still, little is known about in which type of country, and under which circumstances, foreign banks have an advantage over their domestic bank peers. Furthermore, Claessens and van Horen point out that the recent financial crisis has highlighted risks associated with cross-border banking and foreign banks presence. These developments have led to greater interest among policy makers and academicians for more analyses to help guide regulatory reform. Originality/value – The empirical works concerning multinational banking have mainly focused on the determinants and methods of multinational banks entry into foreign markets. On the other hand, empirical evidence on the performance of multinational banks as a subset of the eclectic theory is scarce. By using the whole gamut of foreign subsidiaries of multinational banks operating in the Indian banking sector during the period 2000 to 2008, the paper contributes to this line of the literature.